2014
DOI: 10.3389/fgene.2014.00372
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular functions of the FANCJ DNA helicase defective in cancer and in Fanconi anemia

Abstract: The FANCJ DNA helicase is mutated in hereditary breast and ovarian cancer as well as the progressive bone marrow failure disorder Fanconi anemia (FA). FANCJ is linked to cancer suppression and DNA double strand break repair through its direct interaction with the hereditary breast cancer associated gene product, BRCA1. FANCJ also operates in the FA pathway of interstrand cross-link repair and contributes to homologous recombination. FANCJ collaborates with a number of DNA metabolizing proteins implicated in DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 111 publications
1
76
0
1
Order By: Relevance
“…More recently, we observed that the Fanconi Anemia Group J helicase (FANCJ, also called BACH1 or BRIP1) that is genetically implicated in Fanconi Anemia (FA) as well as breast and ovarian cancer [12,13] is inhibited by a polyglycol modification positioned in the 5′ single-stranded tail, but not the 3′ single-stranded tail, when it is located immediately adjacent to the duplex region of the forked helicase substrate [14]. This finding is consistent with the known 5′ to 3′ directionality of FANCJ translocation on single-stranded DNA [15]. …”
Section: Backbone Modificationssupporting
confidence: 53%
“…More recently, we observed that the Fanconi Anemia Group J helicase (FANCJ, also called BACH1 or BRIP1) that is genetically implicated in Fanconi Anemia (FA) as well as breast and ovarian cancer [12,13] is inhibited by a polyglycol modification positioned in the 5′ single-stranded tail, but not the 3′ single-stranded tail, when it is located immediately adjacent to the duplex region of the forked helicase substrate [14]. This finding is consistent with the known 5′ to 3′ directionality of FANCJ translocation on single-stranded DNA [15]. …”
Section: Backbone Modificationssupporting
confidence: 53%
“…Importantly, of the microsatellites that are unstable in Fancj −/− MEFs, CAG/CTG, TTC/GAA, CA/TG, and CT/AG repeats are potential DNA slippage sites, and CAG/CTG, TTC/GAA, CT/ AG, and CA/TG are believed to form hairpin-like structures, triplex structures, triplex structures, and Z-DNA structures, respectively (Zhao et al 2010). Since FANCJ has been shown to unwind a variety of DNA secondary structures in vitro (Brosh and Cantor 2014), including, but not limited to, hairpins and triplex structures, we propose that FANCJ acts to suppress MSI by dismantling DNA secondary structures that favor repeat sequence expansion or contraction via a strand slippage mechanism (Fig. 7E), which is distinct from error correction by MMR.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most enigmatic FA proteins is FANCJ, a DEAH superfamily 2 helicase and part of the subfamily of Fe-S cluster-containing helicases, which also includes XPD, RTEL1, and CHL1 (Rudolf et al 2006;Gari et al 2012;Brosh and Cantor 2014). Biallelic mutations in FANCJ give rise to FA complementation group J (Levitus et al 2005;Levran et al 2005;Litman et al 2005), whereas monoallelic mutations predispose to ovarian and breast cancers (Seal et al 2006;Rafnar et al 2011).…”
mentioning
confidence: 99%
“…Fanconi anemia is a rare autosomal recessive disorder associated with progressive bone marrow failure, skeletal abnormality and cancer. 16 There was no literature of review or case report about the relationship between BRIP1…”
Section: Discussionmentioning
confidence: 99%